Designing Australian responses to elder abuse: Issues and challenges - Blundell, Barbara; Clare, M. (Springer, 2018)
This chapter explores current national debates about how elder abuse should be defined, and the effect of current definitions on the development of elder abuse responses. It will also examine issues relating to the creation of interventions that meet the needs of an extremely culturally and ethnically diverse population, encompassing both Aboriginal and Torres Strait Islander people as well as migrants from non-English speaking backgrounds. The challenges associated with providing services to remote regional areas will also be discussed. The information in this chapter is based on a body of work conducted in relation to elder abuse in both practice and research over the last decade by the authors, including a number of elder abuse research projects and papers (Black 2008, Clare, Black Blundell, and Clare 2011, Black Blundell and Clare 2012, Clare et al. 2014).